The Decision to Use Sharia Bank with Islamic Financial Literacy and The Mediating Role of Trust - Fitrianingsih, Fitrianingsih; Qorib, Ahmad; Siregar, Saparuddin; Saragih, Lenny Menara Sari (Universitas Dharma Wacana, 2023)
Purpose– The research’s aims to determine the relationship between Islamic financial literacy and customer decisions in choosing Islamic Bank with trust as an intervening variable.Methodology – This is a quantitative research. The data were collected using questionnaire that was distributed to customers and also digged out a variety of good information from articles, journals, books and various other literature sourced from the internet. The The quantity of respondents in this research were 100 people with data analysis techniques using variance-based SEM with Smart Pls 3.0 software. Findings– This research’s reult that the four proposed research hypotheses were accepted, meaning that there was a positive and significant influence from the Islamic financial literacy variable to trust as well as to the decision to choose, trust also had a significant relationship to the decision to choose and the indirect relationship between Islamic financial literacy to the decision to choose through trust. also had a significant relationship. Originality– This study uses Smart Pls in data processing and this research can contribute to Islamic banks in determining factors that can improve customer decisions so that the number of customers is increasing, assets are increasing and the development of Islamic banks is more advanced.